RESPON PERKECAMBAHAN BENIH PADI (Oryza sativa L.) VARIETAS LOKAL KABUPATEN PADANG PARIAMAN HASIL IRADIASI SINAR GAMMA - Henny Puspita Sari; Fatardho Zudri; Winda Purnama Sari (LPPM Universitas Ekasakti, 2024)
Gamma ray irradiation is a mutagenesis method used to obtain new genetic variations in plants, including rice. Local varieties were chosen because they have good adaptability to the local environment and can play an important role in increasing agricultural productivity. The local varieties of rice seeds from Padang Pariaman Regency used in the research were